Model Pastoral Inklusif bagi Umat Tunanetra: Studi tentang Aksesibilitas Liturgi dan Pemberdayaan Komunitas - Yofince Abatan; Yoseph Ludovik Deki Dau; Kasmirus Abatan (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to analyze the relationship between liturgical accessibility, community empowerment, and the spiritual experiences of blind parishioners in fostering meaningful liturgical participation at St. Matthias the Apostle Parish, Tofa. The research employed a qualitative approach with a phenomenological-liturgical ethnography design. The findings reveal that liturgical accessibility remains limited due to the absence of Braille liturgical texts, adaptive audio media, and guiding facilities, causing blind parishioners to depend on verbal assistance and physical accompaniment. Nevertheless, the Blind Basic Ecclesial Community (KUB Tunanetra) plays a significant role in strengthening liturgical competence, self-confidence, spiritual growth, and ecclesial identity through faith formation and active involvement in liturgical ministries. The study concludes that meaningful liturgical participation among blind parishioners can be enhanced through the integration of accessible liturgical facilities, community-based empowerment, and sustainable pastoral accompaniment. These findings lead to the formulation of a Community-Based Inclusive Liturgy Model as a framework for disability-inclusive pastoral ministry.